The role of traditional leadership in supporting municipal service delivery : a case study of Polokwane Municipality in Limpopo Province - Hamusunse, Pamela (University of Limpopo, 2015)
The purpose of this study was to gain a deeper understanding of the role of traditional leaders in supporting service delivery in the communities of Polokwane Municipality as a third sphere of government. Moreover, not much research has been conducted in this field especially in Limpopo Province. The latest policy document on Transforming Public Service Delivery stipulates that public services are not a privilege in a civilised and democratic society, they are a legitimate expectation. Hence, meeting the basic needs of all citizens is one of the five key programmes of the government’s Reconstruction and Development Programme (RDP). From the literature review, it was evident that service delivery is essential in the communities and traditional leaders and the municipality have a critical role to play. Therefore this study also aimed at examining the problems and challenges the community is confronted with during the provision of services and also reflects on the strategic importance of the municipality in service delivery. This information may be used as a point of departure in showing the municipalities and traditional leaders the perception of communities and their level of satisfaction and serves as a yardstick in terms of their effectiveness in delivering services to the community. The study used data collection instruments such as interview schedule, questionnaires and supporting documents, such as the Polokwane Integrated Development Plan and relevant scientific articles to collect data in the four selected villages. The participants ranged from the youth, adults, to people with disabilities and the elderly. The main patterns of concern that emerged from the data related to the low levels of satisfaction among the community in terms of service delivery in general. From the analysis of data it was realised that the lack of proper service delivery impacts negatively on members of the community. It is advisable for the Municipality to take note of these findings and concerns. In an effort to improve and ensure effectiveness in this sphere as stipulated in the White Paper on Transforming Public Service Delivery and the Reconstruction and Development Programme documents. Therefore, it can be concluded that the provision of service delivery in the municipality is of a substandard quality, and that the provision of quality services in the municipality is required. This can be achieved through the participation of traditional leaders, municipalities and community members.
Thesis (MPA. (Public Administration)) -- University of Limpopo, 2015
Keywords: Traditional leaders; Local municipality; Service delivery; Kings and rulers; Chiefdoms; Service delivery